Complex mediascapes, complex realities: critically engaging with biotechnology debates in Ghana. Issue 1 (1st January 2018) - Rock, Joeva
ABSTRACT: The recent increase in research and commercialization of genetically modified (GM) crops in Africa has resulted in considerable and understandable interest from farmers, scholars, and practitioners. However, messy situations are often hard to critically engage in from afar, and the recent article published by Braimah et al. [(2017). Debated agronomy: Public discourse and the future of biotechnology policy in Ghana. Global Bioethics . doi:10.1080/11287462.2016.1261604 ] presents certain claims that further obfuscate – rather than clarify – an already complex landscape. In this commentary I first seek to clarify particular details of the Ghanaian "GMO" (as GM crops are colloquially called in Ghana) story with particular focus on certain actors and their stances. Next, I highlight some methodological shortcomings of Debated Agronomy and correct certain dubious quotations and claims. Finally, I suggest a more ethnographically and discourse-focused methodology to gain much needed insight into how Ghanaians are actively molding, contesting, and questioning GM discourse, funding, and use.